Intention to Engage in Mountain Sport During the Summer Season in Climate Change Affected Environments - Niedermeier, Martin; Frühauf, Anika; Kopp, Martin (Frontiers in Public Health, 2022)
Natural environments can make it easier to engage in regular physical activity, including mountain sport activities. However, global warming is expected to change natural environments, especially in mountainous regions with potential impacts on physical activity behavior. While there is some evidence of a reduced intention to engage in winter sport in climate change affected environments, little is known on the impact of climate change in mountain sports conducted in the summer season. Therefore, the present study aimed at comparing the effect of being exposed to a climate change affected scenario (CCA) to being exposed to a climate change unaffected scenario (CCU) on the intention to engage in summer mountain sport activities. Furthermore, we aimed to analyze the role of anticipated affective responses in the context of the Theory of Planned Behavior (TPB). Using a web-based experimental cross-sectional study design, participants were randomly allocated to scenarios of either CCA or CCU pictures. Participants were asked to complete questions about TPB variables and about affective responses referring to the displayed scenarios. Statistical analyses included tests on group differences and hierarchical linear regression analyses. TPB variables (intention to engage in summer mountain sport, attitude, and perceived behavioral control) did not show significant group differences between CCA (n = 155) and CCU (n = 156), p > 0.131; r < −0.10. Significantly lower anticipated affective valence was found in CCA compared to CCU, p < 0.001, r = −0.43. Affective valence did not significantly improve the TPB model, change in R2 = 0.7%, p = 0.096. However, a higher affective valence was significantly associated with a higher attitude toward summer mountain sport, beta = 0.19, p < 0.001. Intention to engage in summer mountain sport was similar in the groups. Therefore, an immediate reduced engagement in mountain sport activities due to climate change seems unlikely in the summer season, although differentiated findings across various activities of summer mountain sport cannot be excluded. A reduced affective valence during summer mountain sport activities might occur in the presence of signs of climate change in the environment, which may lead to longer-term behavior changes in climate change affected scenarios also in the summer by repeated experiences of reduced valence.